Solving the teacher assignment problem by two Metaheuristics - GUNAWAN, Aldy (Institutional Knowledge at Singapore Management University, 2011)
The timetabling problem arising from a university in Indonesia is addressed in this paper.It involves the assignment of teachers to the courses and course sections. We formulate theproblem as a mathematical programming model. Two different algorithms, mainly basedon simulated annealing (SA) and tabu search (TS) algorithms, are proposed for solving theproblem. The proposed algorithms consist of two phases. The first phase involves allocatingthe teachers to the courses and determining the number of courses to be assigned to eachteacher. The second phase involves assigning the teachers to the course sections in order tobalance the teachers’ load. The performance of the proposed algorithms is evaluated usingtwo sets of real data and some randomly generated problem instances. The computationalresults show that in general, tabu search performs better than simulated annealing and otherprevious work. For the real data sets, the computational results show that both proposedalgorithms yield better solutions when compared to manual allocation done by the university.